Telomerase insufficiency induced telomere erosion accumulation in successive generations in dyskeratosis congenita family. Issue 7 (22nd May 2019) - He, Caixia; Jing, Shuang; Dai, Congling; Tu, Chaofeng; Tan, Zhenhua; Du, Juan; Lu, Guang‐Xiu; Lin, Ge; Zeng, Sicong
Abstract: Background: Dyskeratosis congenita (DC) is a rare heritable bone marrow failure syndrome that is associated with telomere dysfunction, and has high genetic heterogeneity and varied features. Objective: This study aimed to identify the underlying genetic etiology of a DC family with more severe symptoms in the younger generation and to explore the relationship between the genetic causes and the severity of DC phenotype. Methods: Whole‐exome sequencing was performed on the proband to screen the candidate causative gene. The protein structure was then predicted by SWISS‐MODEL software. Telomere length (TL) assay was performed on family members along with large‐scale population controls. The prenatal diagnosis (PND) was performed on the fetus of parents with secondary pregnancy. Results: Novel heterozygous mutations in TERT (NM_198253.2), c.1796G>A (p.Arg599Gln), c.2839T>C (p.Ser947Pro), and c.3346G>C (p.Glu1116Gln) were identified in the proband. His TL was below the first percentile of the peers, which also appeared on the fetus with epidermal dyskeratosis through PND. The TL data of large‐scale population and members of the DC family implied the accumulation of telomere erosion in successive generations in this family. Conclusions: Our study identified three clinical pathologic TERT mutations and implied that telomere erosion might be accumulated through successive generations, contributing to the severity of DC in the younger generation. Abstract : Our study identified three clinical pathologic TERT mutations and implied that telomere erosion might be accumulated through successive generations, contributing to the severity of DC in the younger generation.